2018
DOI: 10.1080/14767058.2018.1430132
|View full text |Cite
|
Sign up to set email alerts
|

Uterine artery Doppler ultrasound in second pregnancy with previous elective cesarean section*

Abstract: CD seems to be associated with increased risks of impaired placental function and circulation and adverse pregnancy outcomes in the subsequent pregnancy, particularly in women with anteriorly located placenta near the previous uterine scar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Moreover, a higher number of patients with increased uterine artery PI values and a higher rate of poor pregnancy outcomes were detected in the group with a history of previous cesarean sections. 13 The results of the study by Torabi et al is consistent with the present study. However, the study group of patients in their study consisted of women with one previous cesarean section and no subgroup analysis was performed regarding the number of previous cesarean sections and uterine artery Doppler PI values.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, a higher number of patients with increased uterine artery PI values and a higher rate of poor pregnancy outcomes were detected in the group with a history of previous cesarean sections. 13 The results of the study by Torabi et al is consistent with the present study. However, the study group of patients in their study consisted of women with one previous cesarean section and no subgroup analysis was performed regarding the number of previous cesarean sections and uterine artery Doppler PI values.…”
Section: Discussionsupporting
confidence: 93%
“…8 Recent studies have investigated the effect of previous cesarean sections on uterine artery Doppler indices in pregnant women, but contradictory results have been revealed. 9,10 To our knowledge, there is no study investigating the relationship between the number of previous cesarean sections and Doppler indices. In this study, we aimed to test the hypothesis that cesarean scarring may increase uterine artery Doppler indices, evaluate the relationship between the uterine artery Doppler indices and the number of previous cesarean sections and analyze its effect on pregnancy complications.…”
Section: Introductionmentioning
confidence: 99%
“…Recent systematic review suggested that UtA-PIs are more consistent and may be more predictive if measured in the second trimester of pregnancy 29 . Therefore a previously published case–control study conducted between 18 and 22 weeks’ gestation that reported the mean ± standard deviation (SD) of UtA-PI in CD (n = 200) and NCD (n = 200) of 1.25 ± 0.4 and 1.16 ± 0.34, respectively ( p = 0.02) was chosen for calculation of sample size 23 . To be conservative, type I error was fixed at a maximum value of 5% and an 80% power, which gave an estimate of 269 participants required for the CD and NCD groups.…”
Section: Methodsmentioning
confidence: 99%
“…Parity, but not route of delivery in previous pregnancies, is an established confounder that needs to be adjusted for the first-trimester mean UtA-PI MoMs as per the FMF’s algorithm 21 , 22 . On the other hand, UtA Doppler measurements in the second (18–22 and 22–24 weeks’ gestation) and third (26–32 weeks’ gestation) trimester of pregnancy demonstrated a trend toward increased uterine vascular resistance in women with previous CD compared to those without previous CD (NCD) 23 – 25 . In theory, laceration or kinking of the UtAs from low-transverse uterine incision and suture repair at the level of uterine isthmus where the left and right UtAs are clinically interrogated as per a standardized technique may explain the consequent changes of UtA hemodynamics 17 .…”
Section: Introductionmentioning
confidence: 99%
“…This provides information that could formulate a causal hypothesis for the observed association. A case control study found that the uterine artery Doppler waveform between 18-22 weeks' gestation is more likely to be notched (14.5% vs. 6%, p<0.001) and have a higher average pulsatility index (1.25 vs 1.16, p<0.02) in women who had an elective CD compared to a VB 31 . Notably, women who had a prior CD also have a higher incidence of preeclampsia 32,33 .…”
Section: Implications (In Light Of Other Evidence)mentioning
confidence: 99%